A Three-Dimensional Finite Element Study on the Biomechanical Simulation of Various Structured Dental Implants and Their Surrounding Bone Tissues - Gong Zhang; Hai Yuan; Xianshuai Chen; Weijun Wang; Jianyu Chen; Jimin Liang; Peng Zhang (International Journal of Dentistry)
Background/Purpose. This three-dimensional finite element study observed the stress distribution characteristics of 12 types of dental implants and their surrounding bone tissues with various structured abutments, implant threads, and healing methods under different amounts of concentrated loading. Materials and Methods. A three-dimensional geometrical model of a dental implant and its surrounding bone tissue was created; the model simulated a screw applied with a preload of 200 N or a torque of 0.2 N·m and a prosthetic crown applied with a vertical or an inclined force of 100 N. The Von Mises stress was evaluated on the 12 types of dental implants and their surrounding bone tissues. Results. Under the same loading force, the stress influence on the implant threads was not significant; however, the stress influence on the cancellous bone was obvious. The stress applied to the abutment, cortical bone, and cancellous bone by the inclined force applied to the crown was larger than the stress applied by the vertical force to the crown, and the abutment stress of the nonsubmerged healing implant system was higher than that of the submerged healing implant system. Conclusion. A dental implant system characterised by a straight abutment, rectangle tooth, and nonsubmerged healing may provide minimum value for the implant-bone interface.